2011
DOI: 10.3174/ajnr.a2429
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Body Detection on CT Angiography

Abstract: BACKGROUND AND PURPOSE: Advances in multidetector CT provide exquisite detail with improved delineation of the normal anatomic structures in the head and neck. The carotid body is 1 structure that is now routinely depicted with this new imaging technique. An understanding of the size range of the normal carotid body will allow the radiologist to distinguish patients with prominent normal carotid bodies from those who have a small carotid body paraganglioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…The first study to characterize the normal CB using CTA was published in 2011. 11 In that study, CB size was not found to correlate with smoking, living at high altitude, age, or sex. Correlation with chronic diseases characterized by sympathetic hyperactivity was not performed in that study.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The first study to characterize the normal CB using CTA was published in 2011. 11 In that study, CB size was not found to correlate with smoking, living at high altitude, age, or sex. Correlation with chronic diseases characterized by sympathetic hyperactivity was not performed in that study.…”
Section: Introductionmentioning
confidence: 74%
“…11 A 20e25% statistically significant enlargement of the CB at CTA in patients with DM, HTN, and CHF was demonstrated relative to control patients. This enlargement is concordant with the low end of enlargement reported in the pathology literature for HTN.…”
Section: Discussionmentioning
confidence: 91%
“…The left carotid body was seen on 86.0% of scans (154 of 179 studies). However, in that study no assessment of the quality of CB imaging was carried out [2].…”
Section: Discussionmentioning
confidence: 97%
“…Nyugen et al evaluated 180 CTAs and they reported that the normal carotid body could be seen on most scans [2]. The right carotid body was seen on 82.6% of CTAs (148 of 179 studies).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation